Identification and Characterization of New Resistance-Conferring SGI1s (Salmonella Genomic Island 1) in Proteus mirabilis - Bie, Luyao; Fang, Meng; Li, Zhiqiang; Wang, Mingyu; Xu, Hai (Frontiers in Microbiology, 2018)
Salmonella genomic island 1 (SGI1) is a resistance-conferring chromosomal genomic island that contains an antibiotic resistance gene cluster. The international spread of SGI1-containing strains drew attention to the role of genomic islands in the dissemination of antibiotic resistance genes in Salmonella and other Gram-negative bacteria. In this study, five SGI1 variants conferring multidrug and heavy metal resistance were identified and characterized in Proteus mirabilis strains: SGI1-PmCAU, SGI1-PmABB, SGI1-PmJN16, SGI1-PmJN40, and SGI1-PmJN48. The genetic structures of SGI1-PmCAU and SGI1-PmABB were identical to previously reported SGI1s, while structural analysis showed that SGI1-PmJN16, SGI1-PmJN40, and SGI1-PmJN48 are new SGI1 variants. SGI1-PmJN16 is derived from SGI1-Z with the MDR region containing a new gene cassette array dfrA12-orfF-aadA2-qacE△1-sul1-chrA-orf1. SGI1-PmJN40 has an unprecedented structure that contains two right direct repeat sequences separated by a transcriptional regulator-rich DNA fragment, and is predicted to form two different extrachromosomal mobilizable DNA circles for dissemination. SGI1-PmJN48 lacks a common ORF S044, and its right junction region exhibits a unique genetic organization due to the reverse integration of a P. mirabilis chromosomal gene cluster and the insertion of part of a P. mirabilis plasmid, making it the largest known SGI1 to date (189.1 Kb). Further mobility functional analysis suggested that these SGIs can be excised from the chromosome for transfer between bacteria, which promote the horizontal transfer of antibiotic and heavy metal resistance genes. The identiﬁcation and characterization of the new SGI1 variants in this work suggested the diversity of SGI1 structures and their significant roles in the evolution of bacteria.